Perbandingan Pengajaran Menggunakan Keterampilan Klinis Video Dengan Keterampilan Klinis Konvensional - Aulia Lukito Wardhani; Andra Novitasari; Mega Pandu Arfiyanti (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
The use of video media in clinical skills education has been implemented at the Faculty of Medicine, Universitas Muhammadiyah Semarang (UNIMUS) since 2019, particularly to enhance students’ understanding and skills in neuromotor physical examination. This study aimed to evaluate the effectiveness of video-based teaching compared to conventional methods in clinical skills learning. A quantitative descriptive method with univariate analysis was used on 138 students who met the inclusion and exclusion criteria. Data were collected from Objective Structured Clinical Examination (OSCE) scores and analyzed using a total sampling technique. The results showed that students who received video-based learning had significantly higher average OSCE scores (93.33 ± 8.918 SD in Block 1) than those who were taught without video media (68.12 ± 15.58 SD in Block 3). In Block 1, 98.6% of the students achieved the “excellent” score category, while only 26.1% of students in Block 3 reached the same level. These findings indicate that the use of teaching videos significantly improves students’ clinical skills and helps overcome the limitations of conventional methods, which tend to promote passive learning. Therefore, the implementation of video-based teaching media can be an effective method to improve the quality of clinical skills education, encourage active student participation, and support the achievement of optimal competencies in medical education. This approach not only enhances skill acquisition but also contributes to more engaging and student-centered learning experiences in the clinical education environment.